El trasegar de enfermería en pro de su sede propia (2012)
Con colaboración de las siguientes exdecanas:Lola Cubillos de Donoso,Irene Esguerra Velandia,Yaneth Mercedes Parrado Lozano,Ana Esperanza Pinzón Castro,Evelyn María Vásquez MendozaAna Luisa Velandia Mora.